Synonymization of subspecies within Anthroherpon cylindricollis complex (Coleoptera: Leiodidae: Leptodirini). - Čeplík, Dávid (Zootaxa, 2026)
The Anthroherpon cylindricollis complex, traditionally (Jeannel, 1924; Jeannel, 1930) divided into three subspecies, Anthroherpon cylindricollis cylindricollis Apfelbeck, 1889, Anthroherpon cylindricollis scaphium Reitter, 1908, and Anthroherpon cylindricollis thoracicum Apfelbeck, 1907, has long presented challenges in terms of taxonomy and subspecies delimitation. In this study, the taxonomic status of these taxa is re‒evaluated primarily on the basis of detailed morphological examination, with supplementary consideration of available molecular data. The analyses reveal only subtle and continuous differences among the three forms, which do not allow reliable separation at the subspecies level. Molecular evidence is consistent with low levels of genetic divergence among the examined populations. A redescription of Anthroherpon cylindricollis, incorporating all previously recognized subspecies and four known populations, is therefore provided. Two subspecies are synonymized herein, and the observed variation is interpreted as geographically structured intraspecific variability.